HEALTH FINANCING ANALYSIS OF MINIMUM SERVICE STANDARDS IN THE HEALTH SECTOR - Risdiyanti, Arie; Paramu, Hadi; Sunarto, Sunarto (Universitas Airlangga, 2024)
Background: This research focuses on health financing Minimum Service Standards (MSS) in the health sector in Lumajang Regency, Indonesia, spanning 2019 to 2022. Despite the government's emphasis on Health MSS, disparities in service access and health conditions persist across different regions. Aims: The research aims to provide insights into the effectiveness of health financing, serving as a foundation for policy recommendations to enhance the efficiency and effectiveness of health fund allocation in Lumajang Regency. Methods: The research employs a quantitative descriptive approach, utilizing DHA and CBA. The study also investigates the budget allocation for MSS Health services. Results: The findings of the research reveal that the realization of Local Original Revenue (LOR) in the Health sector tends to fall below targets. Non-Physical DAK dominate the funding sources in Community Health Centers (Puskesmas). Maternal health services receive the highest MSS Health budget allocation, but the spending proportion relative to total health expenditure is decreasing. Conclusion: The research underscores the importance of addressing disparities in health financing and service access in Lumajang Regency. Recommendations include the diversification of funding sources, optimization of financing at the Puskesmas level, and a reevaluation of the budget allocation for maternal health services. Keywords: CBA, DHA, health financing analysis, minimum service standards